Knowledge, Science, and Literature in Early Modern Germany - Scholz Williams, Gerhild; Schindler, Stephan K. (UNC Studies in the Germanic Languages and Literatures, 1996)
Early modern Germany saw the dissemination of vast quantities of information at unprecedented speed. Popular knowledge, scientific inquiry, and scholarship influenced the political order, poetic expression, public opinion, and mechanisms of social control. This collection presents twelve essays by distinguished scholars regarding the transcendent nature of the Divine, the natural world, the body, sexuality, intellectual property, aesthetics, demons, and witches. The contributors are Thomas Cramer, Walter Haug, C. Stephen Jaeger, Thomas DaCosta Kaufmann, Jan-Dirk Måller, James A. Parente, Jr., Stephan K. Schindler, Gerhard F. Strasser, Lynne Tatlock, Elaine Tennant, Horst Wenzel, and Gerhild Scholz Williams.